Silver surface segregation in Ag-DLC nanocomposite coatings - Manninen, Noora Kristiina (2015)
AgDLC coatings were deposited by magnetron sputtering in order to evaluate: i) the Ag nanoparticle size distribution along the coatings thickness and ii) the silver stability in DLC coatings. Four different coatings were deposited, two AgDLC nanocomposite coatings containing 20 at.% of Ag, with thicknesses of 250 nm and 1000 nm, a 250 nm AgDLC nanocomposite coating with carbon barrier layer of 75 nm and a multilayer coating, consisting of a pure Ag layer with a carbon barrier layer of 75 nm. The coatings were characterized with respect to their structure (by means of X-ray diffraction (XRD)), morphology (by scanning electron microscopy (SEM)) and Ag distribution in depth (by glow discharge optical emission spectroscopy (GDOES)). The AgDLC nanocomposite coatings are composed of Ag nanograins (with a size of about 3 nm) dispersed in an amorphous carbon matrix. The SEM results suggest a bimodal size distribution along the coatings thickness, it was found that Ag forms nanoparticles and aggregates with sizes ranging from 14 nm up to 52 nm on the coating's surface, whereas in bulk, no Ag nanoparticles were visible by SEM. The monitoring of the Ag stability at room temperature conditions during a period of 6 months showed that Ag segregates to the coatings surface, in the AgDLC nanocomposite coating with 1000 nm forming Ag nanofibers, while the thinner AgDLC (250 nm) as well as the multilayer (Ag + DLC and AgDLC + DLC) coatings were stable over time.